Influence of a new method of sterilization on the morphology and physical properties of extracted human teeth - Daylana Pacheco da SILVA; Urias Silva VASCONCELOS; Valdimar da Silva VALENTE; Gregório Antônio Soares MARTINS; Carmem Dolores Vilarinho Soares de MOURA (Universidade Estadual Paulista, 2018)
Abstract Introduction Sterilization methods adopted in Human Teeth Bank can promote structural changes in enamel and dentin. Thus, the ideal method should combine the antimicrobial efficacy and preservation of the substrate biomechanical properties. Aim Evaluated the morphology and physical properties of enamel and dentin of extracted human teeth, after being submitted to different sterilization methods. Method Sixteen extracted third molars were sectioned in the following tooth regions: mesio-distal, vestibular-lingual and at the cement enamel junction. Forty specimens were selected according to values of microhardness and roughness initials, and distributed in four experimental groups (n = 10/group): Group 1 = Autoclave 121 °C (30 minutes); Group 2 = 2.5% Sodium hypochlorite (07 days); Group 3 = 5.25% Sodium hypochlorite (07 days); Group 4= 30% Acetic Acid (7 days). After sterilization, the microhardness, roughness and morphology of enamel and dentin were evaluated. Data were analyzed by paired t-test, Wilcoxon, Kruskal-Wallis and Analysis of Variance. A significance level of 5% was adopted. Result All sterilization methods altered the microhardness and roughness of the dentine (p <0.05). Regarding to enamel, the microhardness was affected only by Autoclave and 2.5% Sodium hypochlorite treatment (p <0.05). A large aperture of the enamel pores and dentinal tubules was verified in the micrographs. Conclusion The sterilization methods adopted altered the morphology and/or physical properties of enamel and dentine.